HER2 assessment in locally advanced gastric cancer: comparing the results obtained with the use of two primary tumour blocks versus those obtained with the use of all primary tumour blocks. Issue 4 (19th July 2017) - Xu, Chen; Liu, Yalan; Jiang, Dongxian; Ge, Xiaowen; Zhang, Ying; Su, Jieakesu; Zeng, Haiying; Huang, Jie; Ji, Yuan; Hou, Jun; Sun, Yihong; Shen, Kuntang; et al.
Abstract : Aims: HER2 is currently the only biomarker used to select eligible patients with advanced gastric cancer (GC) for targeted therapy. The aims of this study were to verify the value of dual‐block HER2 assessment and to explore whether increasing the block number is more beneficial by carrying out a randomized prospective cohort study in which dual‐block and all‐block HER2 assessment were compared in resected specimens of GC. Methods and results: Five hundred and forty‐nine resected GC specimens were randomly enrolled into two cohorts: a dual‐block group ( n = 274) with two primary tumour blocks tested, and an all‐block group ( n = 275) with all primary tumour blocks tested. Immunohistochemical staining of HER2 was performed. For HER2‐equivocal (2+) cases, fluorescence in‐situ hybridization (FISH) was performed. As compared with single‐block assessment, dual‐block assessment increased the HER2 immunohistochemistry (IHC)‐positive (3+) rate. The rate with dual‐block assessment (11.3%) was significantly higher than that with block 1 assessment (8.8%) ( P = 0.016) and block 2 assessment (9.1%) ( P = 0.031). Similarly, all‐block assessment demonstrated a higher HER2 3+ rate (12.4%) than single‐block assessment (block 1, 6.5%; block 2, 6.2%; block 3, 7.2%; block 4, 8.7%) ( P < 0.05). HER2 3+ rates of all‐block and dual‐block assessments showed no significant difference ( P = 0.703). After IHC and FISH results had been combined, the HER2‐positive rate with all‐block assessment (13.5%) was slightly higher than that with dual‐block assessment (12.0%), although the difference was not statistically significant ( P = 0.62). Conclusions: Dual‐block immunohistochemical assessment is an effective, practical and economic approach that is suitable for the preliminary screening of HER2. We recommend that dual‐block HER2 assessment be routinely performed on resected specimens of GC. All‐block assessment can be a supplement to dual‐block assessment if necessary.